Dielectric and microwave absorption properties of plasma sprayed Cr/Al2O3 composite coatings. Issue 10 (December 2015) - Zhou, Liang; Cui, Shan; Zhai, Ying; Luo, Fa; Dong, Yangyang
Abstract: Cr/Al2 O3 coatings were fabricated by plasma spraying technology from ball milled and spray dried feedstock powders, and their microstructure, complex permittivity and microwave absorption properties were investigated. The results show that Cr particles were uniformly distributed throughout the coating with the evidence of pores, cracks and a few light contrast stringers. The complex permittivity of Cr/Al2 O3 coatings increased with increasing Cr volume fraction, and the coating with higher chrome content exhibited visible frequency-dependent dielectric response. The minimum reflection loss ( RL min ) shifted to a lower frequency region with the increase of chrome content and coating thickness. RL min of the coating with 15 vol% Cr reached –33.3 dB at 8.8 GHz and the reflection loss values below –10 dB could be obtained in the frequency range from 8.2 to 9.7 GHz when the coating thickness was 1.7 mm. These results imply that the microwave absorption properties can be manipulated by tuning the coating thickness and permittivity values.